2020
DOI: 10.1021/acsaem.0c02098
|View full text |Cite
|
Sign up to set email alerts
|

Space-Confined Synthesis of Yolk–Shell Structured Co3O4/Nitrogen-Doped Carbon Nanocomposites with Hollow Mesoporous Carbon Nanocages as Advanced Functional Anodes for Lithium-Ion Batteries

Abstract: Despite the high theoretical capacity as the anode material of lithium-ion batteries (LIBs), Co 3 O 4 is subjected to rapid capacity decline and poor rate performance owing to its severe volume expansion and poor electronic conductivity. Herein, a yolk− shell structured Co 3 O 4 nanocomposite with double carbon shells (Co 3 O 4 @NC@CNC) was fabricated as an electrode material to improve the properties of LIBs. The Co 3 O 4 @ NC@CNC was derived from ZIF-67 within carbon nanocages (CNC) by carbonization. The hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…In charge‐discharge cycles, carbon shell or carbon skeleton type structures precisely confine the volume change of active materials particles while the mesopores and conductive walls provide efficient mass transport and fast charge transfer routes. These mesoporous structures can also serve as nanoreactors to regulate the in situ growth of active materials during the synthesis process, which can precisely downsize the active material NPs and further improve the anode electrochemical performance [115,118] . d), Utilizing the 2D carbon to synthesize sandwich‐like mesoporous structure [123,124] .…”
Section: Lithium Batteriesmentioning
confidence: 99%
See 3 more Smart Citations
“…In charge‐discharge cycles, carbon shell or carbon skeleton type structures precisely confine the volume change of active materials particles while the mesopores and conductive walls provide efficient mass transport and fast charge transfer routes. These mesoporous structures can also serve as nanoreactors to regulate the in situ growth of active materials during the synthesis process, which can precisely downsize the active material NPs and further improve the anode electrochemical performance [115,118] . d), Utilizing the 2D carbon to synthesize sandwich‐like mesoporous structure [123,124] .…”
Section: Lithium Batteriesmentioning
confidence: 99%
“…The performance of these electrodes was, therefore, be further improved compared to strategy a) [104,110–114] . c), Hollow MCs were served as nanocages to encapsulate active materials [36,55,69,105,115–122] . In charge‐discharge cycles, carbon shell or carbon skeleton type structures precisely confine the volume change of active materials particles while the mesopores and conductive walls provide efficient mass transport and fast charge transfer routes.…”
Section: Lithium Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“… 10 For example, space-confined synthetic approaches were used to obtain various types of yolk–shell particles. 11 14 Past studies have showed that different functional substances, such as therapeutic agents, can be incorporated into yolk–shell nanoparticles. 15 , 16 However, most of the current synthetic approaches involve multistep synthetic procedures, including thermal treatment and/or chemical etching.…”
mentioning
confidence: 99%